2014
DOI: 10.1021/je5008789
|View full text |Cite
|
Sign up to set email alerts
|

New Experimental Data and Reference Models for the Viscosity and Density of Squalane

Abstract: Empirical models for the density and the viscosity of squalane (C30H62; 2,6,10,15,19,23-hexamethyltetracosane) have been developed based on an exhaustive review of the data available in the literature and new experimental density and viscosity measurements carried out as a part of this work. The literature review showed there was a substantial lack of density and viscosity data at high temperature (373 to 473) K and high pressure conditions (pressures up to 200 MPa). These gaps were addressed with new experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
93
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(97 citation statements)
references
References 76 publications
4
93
0
Order By: Relevance
“…The approach assumes an analytic form for the shear-rate-dependent viscosity that is validated by comparing to the unusually large set of nonequilibrium and equilibrium flow measurements for squalane (19,20,(22)(23)(24)(25)(26)(27). Newtonian viscosities are obtained from two-parameter fits of this analytic form to the high-rate response.…”
mentioning
confidence: 99%
“…The approach assumes an analytic form for the shear-rate-dependent viscosity that is validated by comparing to the unusually large set of nonequilibrium and equilibrium flow measurements for squalane (19,20,(22)(23)(24)(25)(26)(27). Newtonian viscosities are obtained from two-parameter fits of this analytic form to the high-rate response.…”
mentioning
confidence: 99%
“…It is therefore essential for the calibration of the three sensors. Unfortunately, it was found that none of the three reference correlations [62,63] represents the IC data set within its estimated expanded uncertainty of 2 % [63]. Rather, the combined range of deviations from the three correlations is from −7.8 % to +7.4 %.…”
Section: Calibration With Squalanementioning
confidence: 96%
“…Mylona et al [62] published two reference correlations for the viscosity of squalane, one formulated in terms of temperature and density and one formulated in terms of temperature and pressure. Schmidt et al [63] published a third reference correlation in terms of temperature and pressure and an additional viscosity data set that was measured at Imperial College (IC), London (UK) with a vibrating wire viscometer in the temperature range from 338.2 K to 473 K with pressures up to 200 MPa. This data set is the only one that overlaps with the temperature and pressure range of the viscometer used at NIST.…”
Section: Calibration With Squalanementioning
confidence: 99%
“…The viscosity of a reference liquid, squalane, has been extensively measured to high pressure in various laboratories [34][35][36][37]. A correlation using the McEwen model in reference [34] yielded parameters at 65°C of 0  6.82 mPa·s, q  6.88 and *  14.77 GPa -1 . The deviations of this correlation from data of three publications [35][36][37] are plotted in Figure 6,…”
Section: Limitations Of the Mcewen Modelmentioning
confidence: 99%